Lipofectin increases the efficiency of DNA-mediated transformation of Neurospora crassa - C. P. SELITRENNIKOFF; M. S. SACHS (Fungal Genetics Reports, 1991)
Transformation of N. crassa using the calcium chloride/polyethylene glycol procedure (Fincham 1989. Microbiol. Rev. 53:148-170) can yield 100-10,000 transformants per microgram of input DNA when integration occurs nonhomologously, and considerably lower numbers of transformants when homologous integration of DNA is required. Increasing the efficiency of transformation would be useful for screening cosmid libraries and for obtaining transformants from homologous integration events. In addition, strains that transform poorly using standard procedures, e.g. the cell-wall-less derivatives of os-1 (Phelps et al. 1990 Curr. Microbiol. 21:233-242) would benefit from improvements in the transformation procedure.